2023
DOI: 10.21203/rs.3.rs-2474576/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bibliometric analysis of the global scientific production on machine learning applied to different cancer types

Abstract: Cancer disease is one of the main causes of death in the world, with million annual cases in the last decades. The need to find a cure has stimulated the search for efficient treatments and diagnostic procedures. One of the most promising tools that has emerged against cancer in recent years is Machine Learning (ML), which has raised a huge number of scientific papers published in a relatively short period of time. The present study analyzes global scientific production on ML applied to the most relevant cance… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
0
0
Order By: Relevance
“…A lack of cross-border cooperation among institutions were found in our analysis. In fact, not only in the field of glioma research (42), but also in many other fields, bibliometrics studies have suggested researchers to break national boundaries and enhance communication and collaboration (43)(44)(45). This problem may be caused by language communication barriers and the long space distance.…”
Section: Discussionmentioning
confidence: 99%
“…A lack of cross-border cooperation among institutions were found in our analysis. In fact, not only in the field of glioma research (42), but also in many other fields, bibliometrics studies have suggested researchers to break national boundaries and enhance communication and collaboration (43)(44)(45). This problem may be caused by language communication barriers and the long space distance.…”
Section: Discussionmentioning
confidence: 99%